Functional Engineering of Perovskite Nanosheets: Impact of Lead Substitution on Exfoliation in the Solid Solution RbCa2–xPbxNb3O10. Issue 21 (7th November 2017) - Ziegler, Christian; Dennenwaldt, Teresa; Weber, Daniel; Duppel, Viola; Kamella, Claudia; Podjaski, Filip; Tuffy, Brian; Moudrakovski, Igor; Scheu, Christina; Lotsch, Bettina V.
Abstract : Tuning the chemical composition and structure for targeted functionality in two‐dimensional (2D) nanosheets has become a major objective in the rapidly growing area of 2D materials. In the context of photocatalysis, both miniaturization and extending the light absorption of UV active photocatalysts are major assets. Here, we investigate the solid solution between two photocatalytic systems known from literature to evolve H2 from water/methanol under UV – RbCa2 Nb3 O10 ( E g = 3.7 eV) – and visible light irradiation – RbPb2 Nb3 O10 ( E g = 3.0 eV) – by synthesizing hypothetical RbCa2– x Pb x Nb3 O10 . While the calcium niobate can easily be exfoliated into individual nanosheets via cation–proton exchange and subsequent treatment with tetra‐ n ‐butylammonium hydroxide (TBAOH), the lead niobate barely yields nanosheets. Spectroscopic and microscopic analysis suggest that this is caused by volatilization of Pb during synthesis, leading to a local 3D linkage of RbPb2 Nb3 O10 perovskite units with Pb deficient units. On the one hand, this linkage progressively prevents exfoliation along with an increasing Pb content. On the other hand, introducing Pb into the perovskite blocks successively leads to bandgap narrowing, thus gradually enhancing the light harvesting capability of the solid solution. Finding a compromise between this narrowing of the bandgap and the possibility of exfoliation, visible light sensitized nanosheets can be engineered in good yield for an initial molar ratio of Ca:Pb ≥ 1:1. Abstract :